Kesantunan Berbahasa dalam Tindak Tutur Ekspresif Teks Sketsa Komedi pada Kanal Youtube Praz Teguh - Silva Hasma Junianti; Ermanto Ermanto (Persona: Kajian Bahasa dan Sastra, 2022)
Praz Teguh is West Sumatra influencer who has received controversy over the principle of language politeness expressive speech he speaks on social media. This study is aimed at describing the form of expressive speech acts, the function of expressive speech acts, and the obeys and violates of language politeness using Leech's theory. The primary data is sourced from humorous speech derived from 4 videos of Pacah Paruik's comedy sketch content uploaded in May-October on 2021 by listening to the video repeatedly, retyping like a drama script, and providing contexts to help writers when at classificated the data. This methode in this research is a descriptive qualitative based on existing data. The results obtained of this study indicate that there are (1) forms of expressive speech acts, which consists of anger; criticize; thank; praise; complain; and apologizing, (2) forms of expressive speech acts functions consists of joy; difficulty; admiring; reproach; and regret, (3) forms of obeys and violates of the principal of politeness found on the Praz Teguh YouTube channel.